The Effect of ESG on Bank Performance: The Moderating Role of Foreign Ownership - Serly; Tang, Sukiantono; Duha, Novit Cahyesi (Gorontalo Accounting Journal, 2026)
This study aims to analyze the impact of ESG on bank performance as measured by Return on Assets (ROA), Return on Equity (ROE), and GRI disclosure index with foreign ownership as a moderator. The research sample uses data from companies engaged in the banking sector in Indonesia with an observation period from 2019 to 2023. The research approach used is moderation regression analysis with secondary data from annual reports and sustainability reports. This study finds that foreign ownership can strengthen the positive influence of ESG on bank performance. This indicates that the involvement of foreign investors can strengthen the implementation of sustainability practices through better external oversight mechanism.